Intra- and interindividual variation in the advertisement call of Dendropsophus banner (Cochran, 1948) (Anura: Hylidae) - de Oliveira-Santos, José Ricardo; de Araújo, Alan Pedro; de Moraes, Maísa Maria; de Santana, Adsson Rodrigues; Rocha, Eric Bernardino Gadelha; Dias, Emerson Gonçalves; Leandro-Silva, Victor; Da Silva Oliveira, Alan Jefferson; de Moura, Geraldo Jorge Barbosa; Gambale, Priscila Guedes (Zootaxa, 2020)
Vocalization is one of the main behaviors of anurans (Köhler et al. 2017). Calls emitted by these animals display several social and ecological functions. For example, they can be used for attraction of conspecific females (Toledo et al. 2015) and territorial defense (Wells 2010). Advertisement calls are emitted predominantly by males (Kelley 2004) and constitute a key-factor for species identification (Köhler et al. 2017).